VALIDITAS HANDOUT BERBASIS PENEMUAN TERBIMBING PADA PERKULIAHAN EVALUASI PROSES DAN HASIL BELAJAR BIOLOGI - Siska Nerita; Yulia Sri Hartati; Annika Maizeli; Aulia Afza (Jurnal Penelitian Pendidikan IPA, 2018)
Some problems found in Process Evaluation and Learning Outcomes of Biology was the student difficult to understand the subject, the media that used in learning was power point, and the subject unavailability of learning resources that can guide and make students independent study. Thus it necessary to develop of handout based on guided discovery method. The purpose of this research was to develop handout based on guided discovery method on Process Evaluation and Learning Outcomes of Biology subject. This was development research with use 4D model. This research is limited in the Develop phase for know the validity of handout. The instruments is handout validity analysis questionaire. Data analysis use percentage formula. The result show that validity of handout was 89,38 with high valid criteria. It can be concluded that handout based on guided discovery method had been valid.Keywodrs : validity, handout, guided discovery method